CFD and Experimental Analysis of Swirl Type Single‐Fluid Atomizer for Optimization of Recrystallization Process to Make Ultrafine RDX Explosive. Issue 1 (11th October 2019) - Goyal, Varun; Gupta, Shallu; Kumar, Pal Dinesh; Jindal, Deepika; Singh, Gokul; Agarwal, Arun; Lata, Prem
Abstract: In this research work, a novel idea of using a pressure swirl single‐fluid atomizer is used for the preparation of ultrafine 1, 3, 5‐Trinitro‐1, 3, 5‐triazinane or formally cyclotrimethylenetrinitramine (RDX) explosive using the solvent/ anti‐solvent method with reaching a milestone development of a numerical model to determine the particle size. A theoretical analysis is performed and referred to compute the optimum dimensions of the atomizer and a detailed numerical and experimental investigation is presented. Computer‐Aided‐Design (CAD) and Computational Fluid Dynamics (CFD) is used to model and simulate the flow of solvent through the atomizers in order to determine the most important parameters like the Sauter Mean Diameter (SMD) of the droplets, Turbulent Dissipation Rate, Turbulent Kinetic Energy and the exit velocity through the atomizer. Ultrafine RDX explosive is recrystallized with a mean particle size of 4.99 μm and a standard deviation of 1.35 μm. The experimental process performed using the fabricated atomizer is a laboratory scale table‐top pilot plant which is simple, cost‐effective, and safe. It is then observed that this numerical model accurately predicts the particle size from the designed atomizer when compared to the experimentally obtained particle size with the difference lying between 1 % and 5 %. Abstract :